The role of TLR2 in exercise-induced immunomodulation in normal weight individuals - Fatemah Bahman; Halemah AlSaeed; Shaima Albeloushi; Fahd Al-Mulla; Rasheed Ahmad; Fatema Al-Rashed (Scientific Reports, 2023)
Abstract Toll-like receptors (TLRs) have been targeted for therapeutic drug development for several disorders, including cardiovascular diseases (CVD), and diabetes mellitus. Daily levels physical activity (PA) has been purported to influence the systemic circulation of cytokines, affecting the overall activation of TLRs and influencing the inflammatory milieu. Objective and self-reported daily PA was tracked in 69 normal-weight adults. Freedson's cut-offs categorized daily PA intensity into the 25th lowest, medium, and top percentiles. Monocytic TLR2 expression was quantified by flow cytometry in fresh whole blood. Cross-sectional associations between flow cytometry measured TLR2+ subsets and clinical biomarkers were evaluated. PA increased circulation of TLR2+ monocytes. TLR2 expression was adversely corelated with reduced diastolic blood pressure (DBP), triglyceride (TG), and matrix metallopeptidase 9 (MMP9) levels. However, regression analysis indicated that only TG levels were independently linked with TLR2+ subsets in circulation in active participants. Higher daily levels of physical activity are associated with improved cardiovascular blood markers and elevated circulatory monocytic TLR2+ subsets. These findings suggest that TLR2 may play a role in modulating CVD risk factors in individuals leading physically active lifestyles.